Homeostatic Cytokines Drive Epigenetic Reprogramming of Activated T Cells into a “Naive-Memory” Phenotype - Guido Frumento (iScience, 2020)
Summary: Primary stimulation of T cells is believed to trigger unidirectional differentiation from naive to effector and memory subsets. Here we demonstrate that IL-7 can drive the phenotypic reversion of recently differentiated human central and effector memory CD8+ T cells into a naive-like phenotype.These “naive-revertant” cells display a phenotype similar to that of previously reported stem cell memory populations and undergo rapid differentiation and functional response following secondary challenge. The chromatin landscape of reverted cells undergoes substantial epigenetic reorganization with increased accessibility for cytokine-induced mediators such as STAT and closure of BATF-dependent sites that drive terminal differentiation. Phenotypic reversion may at least partly explain the generation of “stem cell memory” CD8+ T cells and reveals cells within the phenotypically naive CD8+ T cell pool that are epigenetically primed for secondary stimulation. This information provides insight into mechanisms that support maintenance of T cell memory and may guide therapeutic manipulation of T cell differentiation. : Biological Sciences; Molecular Biology; Immunology Subject Areas: Biological Sciences, Molecular Biology, Immunology